Monitoring blood biomarkers and training load throughout a collegiate soccer season - Huggins, A. R.; Fortunati, R.; Curtis, M. R.; Looney, P. D.; West, A. C.; Lee, C. E.; Fragala, S. M.; Hall, L. M.; Casa, J. D. (The Journal of Strength and Conditioning Research, 2019)
This observational study aimed to characterize the responses of a comprehensive panel of biomarkers, observed ranges, training load (TL) metrics, and performance throughout the collegiate soccer season (August-November). Biomarkers (n = 92) were collected before the start of pre-season (PS), in-season weeks (W)1, W4, W8, and W12 in NCAA Division I male soccer players (n = 20, mean ± SD; age = 21 ± 1 years, height = 180 ± 6 cm, body mass = 78.19 ± 6.3 kg, body fat = 12.0 ± 2.6%, VO2max 51.5 ± 5.1 ml·kg·min-1). Fitness tests were measured at PS, and W12 and TL was monitored daily. Changes in biomarkers and performance were calculated via separate repeated-measures analysis of variance. Despite similar fitness (p > 0.05), endocrine, muscle, inflammatory, and immune markers changed over time (p < 0.05). Total and free testosterone was lower in W1 vs. PS, whereas free cortisol remained unchanged at PS, W1, and W4 (>0.94 mg·dL-1). Oxygen transport and iron metabolism markers remained unchanged except for HCT (W1 vs. PS) and total iron binding capacity (W8-W12 vs. W1). Hepatic markers albumin, globulin, albumin:globulin, and total protein levels were elevated (p < 0.05) at W12 vs. W1, whereas aspartate aminotransferase and alanine aminotransferase levels were elevated at W1-W12 and W8-W12 vs. PS, respectively. Vitamin E, zinc, selenium, and calcium levels were elevated (p < 0.05) at W12 vs. W1, whereas Vitamin D was decreased (p < 0.05). Fatty acids and cardiovascular markers (omega-3 index, cholesterol:high-density lipoprotein [HDL], docosahexenoic acid, low-density lipoprotein [LDL], direct LDL, non-HDL, ApoB) were reduced at W1 vs. PS (p = 0.05). Immune, lipid, and muscle damage biomarkers were frequently outside clinical reference ranges. Routine biomarker monitoring revealed subclinical and clinical changes, suggesting soccer-specific reference ranges. Biomarker monitoring may augment positive adaptation and reduce injuries from stressors incurred during soccer.